FUNGITOXITY OF Mentha spicata OIL ON THE GROWTH OF FUNGI OF THE GENERA Colletotrichum AND Fusarium (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Increasingly, the population has been concerned that the production of these foods is free of pesticide residues, so it is necessary to search for viable and effective alternatives to control pests and diseases. Thus, the use of essential oil from plants with insecticidal and fungicidal potential has been successfully studied. The study aimed to demonstrate the effect of Mentha spicata essential oil on the control of Fusarium and Colletotrichum fungi in vitro. The essential oil of M. spicata used was purchased from the chemical industry Ferquima, being diluted in a 2% Tween 20 solution (being 98 mL of distilled water + 2 mL of Tween 20), which was added in 60 mL of a PDA culture medium, resulting in final essential oil concentrations: 0 ppm; 0.83 ppm; 1.67 ppm; 8.33 ppm, and 16.67 ppm and poured into 90 mm diameter Petri dishes. The evaluations took place periodically every 48 hours for eight days, performing measurements of the diameters of the colonies. The results evidenced that the analyzed fungi, when submitted to treatments of different doses, suffered fungistatic action according to the gradual increase of the doses. Thus, it is possible to conclude that M. spicata oil provided the in vitro growth control of Fusarium sp. and Colletorichum sp.